A new deer species (Cervidae, Mammalia) from the upper Siwaliks (Pakistan). (10th September 2021) - Croitor, Roman; Abbas, Sayyed Ghyour; Babar, Muhammad Adeeb; Khan, Muhammad Akbar
Abstract: The article presents a description of a new species of the genus Praesinomegaceros from the Early Pleistocene of Pabbi Hills (Upper Siwaliks) in Pakistan. This is a first record of Praesinomegaceros in the geological past of the Indian Subcontinent. Unlike Praesinomegaceros from the Late Miocene of Central Asia, the Siwalik form is characterized by the loss of basal tine palmation and diminished number of crown ramifications. However, the new Siwalik cervid maintains the characteristic of Praesinomegaceros general antler bauplan. The antler shape of the new species from Pakistan reveals important evolutionary changes in ecology and ethology. Antlers of Praesinomegaceros from Siwaliks have lost their function of social display and "returned" to the effective weapon antler type. The multivariate cluster analysis of antler characters supports the close evolutionary relationship of the new cervid species from the Siwaliks with Praesinomegaceros and Sinomegaceros from the Pleistocene of Asia.